Production and Marketing Management of MSME Rattan and Palm Stick Handicrafts Andini - Arisman; Sudarmiatin (Journal of Research in Business, Economics, and Education, 2021)
This activity aims to examine the condition of the Rattan and Palm Stick Handicraft "Andini". especially those related to production and marketing systems, business potentials and opportunities, as well as challenges and the government's role in efforts to increase these MSMEs. The visit was made to the Small and Medium Enterprises of Rattan and Palm Oil Crafts "Andini" in Sungai Salak Hamlet, Marga Mulya Village, Rambah Samo District, Rokan Hulu Regency, Riau Province with an implementation time of 16 September 2021. The methods used for data collection were observation, documentation and interviews. The results of this visit provide an illustration that snacks in SMEs are still traditional, but there are potentials and potential opportunities in this business. Rattan and Palm Sticks Handicraft "Andini" is economically quite profitable. However, there are still challenges and financial constraints related to working capital felt by MSMEs and the need for local government participation in efforts to increase these MSMEs.